Efektivitas Penggunaan Model Problem Based Learning untuk Meningkatkan Keterampilan Sosial Anak Usia 5-6 Tahun - Utami, Dian Tri; Raihana, Raihana; Alucyana, Alucyana; Nisa, Kudwatun; Rofi'atin, Siti (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
It is important for children to master social skills from an early age as a provision for interacting with the environment and adapting themselves to the norms and values that apply in society. It requires experience and practice included in learning activities to enable children to interact and improve social skills. The problem-based learning model is a learning model that can expose children to social problems which is done in small groups which requires cooperation in an effort to find solutions to solve problems. The aim of the research is to examine the effect of problem based learning on the social skills of children aged 5-6 years. The research method uses an experiment with a quasi-experimental design, there are control and treatment groups, pretest and posttest. The results of the research show that there is an influence of problem-based learning on children's social skills.